Elranatamab versus physician’s choice of treatment in patients with triple-class exposed/refractory multiple myeloma: an updated matching-adjusted indirect comparison - Isha Mol; Yannan Hu; Thomas W LeBlanc; Joseph C Cappelleri; Haitao Chu; Guido Nador; Didem Aydin; Isabel Perez Cruz; Patrick Hlavacek (Journal of Comparative Effectiveness Research)
Aim: Despite the availability of novel treatment options for patients with triple-class exposed/refractory multiplemyeloma , there is a lack of consensus on the optimal regimen. A previous unanchored matchingadjusted indirect comparison (MAIC) of the MagnetisMM-3 (NCT04649359) and LocoMMotion (NCT040 35226) study reported significant improvements in progression-free survival (PFS) and overall survival (OS) with elranatamab versus physician’s choice of treatment. Materials & methods: We conducted an updated MAIC based on more recent data (28.4 months for MagnetisMM-3). Following reweighting of MagnetisMM-3 individual patient data to match the LocoMMotion population, the effective sample size was 64 for PFS and 63 for OS in the base-case analysis. Results: Consistent with the original MAIC, significantly improved PFS (hazard ratio [HR] [95% confidence interval (CI)]: 0.32 [0.21, 0.50], p < 0.01) and OS (HR [95% CI]: 0.50 [0.33, 0.78], p < 0.01) were observed with elranatamab versus physician’s choice of treatment. The robustness of the results was demonstrated in sensitivity analyses in whichmissing baseline characteristics data for elranatamab were imputed. Conclusion: Overall, the findings of this study align with and add confidence to the conclusions of the previous MAIC that elranatamab is associated with significantly improved outcomes versus standard treatment, supporting the value to elranatamab for the treatment of patients with triple-class exposed/refractory multiple myeloma.